Studying political discourse of the President address in Russia with the text mining technique (Journal of Philosophy Culture and Political Science, 2020)
The article describes the technique and results of the study of political discourse using text miningtechnology with the statistical package R. Unlike traditional content analysis, text mining uses automatedmethods for processing text in natural languages. The article presents a specific technique of computationaloperations and an algorithm of visualization. The study aims to study the corpus of texts of thePresident Address to the Federal Assembly in Russia. The study describes the evolution of the politicalagenda in post-Soviet Russia within the discourse analysis approach. The study shows that the idea of‘democracy and human rights’ fails to be the key concepts of public policy in Russia. The presidents ofRussia usually stick around 3 common topics: Russia, state, and power. The author approves that textmining allows us to automate part of the research work and it functions as one of the directions for acomprehensive analysis of political discourse. The applied technique can be used to automate researchin political linguistics, as well as to study different types of political documents and texts.Key words: text mining, political discourse, president address, political communication, mathematicallinguistics.